An improved shuffled frog leaping algorithm and its application in the optimization of cascade reservoir operation. Issue 15 (10th December 2018) - Li, Rongbo; Jiang, Zhiqiang; Li, Anqiang; Yu, Shan; Ji, Changming
ABSTRACT: A new improved shuffled frog leaping algorithm (SFLA), the chaos catfish effect SFLA (CCESFLA), is proposed by coupling a local "refine search" mechanism and a "global incentive adjustment" mechanism. Chaotic technology is introduced in the local "refine search" mechanism to improve local search ability, by implementing more refined local search around the optimal individuals. The catfish effect mechanism is adopted in the "global incentive adjustment" mechanism to improve global convergence, by motivating the frogs to "jump out" of the local steady state. The operation optimization by the CCESFLA is carried out taking the Li Xianjiang cascade reservoirs in China as an example. Compared with SFLA, particle swarm optimization, immune SFLA and cloud SFLA, the average annual power generation using the CCESFLA can be increased by 6.7, 7.5, 3.0 and 0.8%, respectively. The convergence process of the CCESFLA is more stable, and its execution time is the least of the three improved SFLAs.